(untitled) (Journal of research in medical and health sciences, 2025)
With the proliferation of digital media, pathological gaming behavior among junior high school students has become a growing social concern. From the perspective of academic stress, this study explores its relationship with pathological gaming behavior, with a specific focus on the sequential mediating roles of emotional regulation difficulties and escape motivation. A questionnaire survey was conducted among 650 junior high school students using the Academic Stress Scale, Difficulties in Emotion Regulation Scale, Gaming Escape Motivation Scale, and Pathological Gaming Behavior Scale. The results indicated that: (1) Academic stress, emotional regulation difficulties, escape motivation, and pathological gaming behavior were all significantly positively correlated with each other. (2) Academic stress could not only directly predict pathological gaming behavior but also influence it through three indirect pathways: the separate mediating effect of emotional regulation difficulties, the separate mediating effect of escape motivation, and the sequential mediating effect of emotional regulation difficulties → escape motivation. This study constructs a sequential mediation model, revealing the influencing pathway of "academic stress → emotional regulation difficulties → escape motivation → pathological gaming behavior," providing a theoretical basis and practical insights for understanding and intervening in excessive gaming among junior high school students.